Theory and practice of curriculum studies - Lawton, Denis; Gordon, Peter; Ing, Maggie; Gibby, Bill.; Pring, Richars; Moore, Terry (London : Routledge & Kegan Paul, 1978)
This book deals with curriculum issues and problems, and one of its aims is to help practising teachers to clarify their own theory and practice in relation to the curriculum. The contributors look at three popular theories or sets of assumptions held by teachers: the child-centred view of education; the subject-centred or knowledge-centred view; and the society-centred view. Each of these views is incomplete on its own, but each has something to contribute in planning a curriculum as a whole, and the authors emphasize that a comprehensive theory of curriculum planning would take into account.
Includes bibliographical references and index.
Keywords: Curriculum planning